PENGARUH PEMBERIAN TELUR BEBEK DENGAN KONSENTRASI BERBEDA TERHADAP MUTU BAKSO DAGING LIMBAH FILLET IKAN KAKAP MERAH (Lutjanus sanguineus) - Ramli Ramli (Samakia : Jurnal Ilmu Perikanan, 2013)
Research conducted at the Laboratory of Fishery Products Processing Technology Aperik Ibrahimy and laboratory of Agricultural Technology UB Malang. The materials used in this study is the meat waste meat red snapper (Lutjanus sanguineus) 1 kg, duck eggs (10%, 20% and 30% of the weight of the dough. From this study showed that the addition of concentration duck egg provides real difference the color, aroma, protein content, water and fat. From the results, it can be concluded that the best concentration of the addition of a duck egg on fish balls is 10%.